Complete inclusion of adaptive rowing only 1000 m ahead. Issue 13 (5th August 2013) - Smoljanovic, Tomislav; Bojanic, Ivan; Hannafin, Jo A; Urhausen, Axel; Theisen, Daniel; Seil, Romain; Lacoste, Alain
Abstract : Adaptive rowing (AR) at the Paralympic level is accessible for rowers with physical disability. AR was included for the first time in the Beijing 2008 Paralympic Games. Racing distance for all AR events is currently 1000 m, which impedes public recognition of this sport and leads to many organisational challenges during the inclusive World Rowing Championships. The aim of this report was to discuss the feasibility of increasing AR race distance to 2000 m from a sports injury and athletic health perspective. As limited data on injury and illness risks exist in AR, knowledge and experiences had to be taken from other Paralympic sports. The anticipated duration of 2000 m AR competitions is either comparable or considerably lower than that of the other Paralympic disciplines with similar characteristics. AR has inherent injury and health risks especially within thorax, shoulders and low back region, but they are not expected to be significantly modified by increased racing times. Specific considerations need to be taken into account for athletes with a spinal cord injury, like in other sport disciplines. There are no distinctive contra-indications for AR events of 2000 m based on the current literature review and a 10-year experience in this sport. Long-term follow-ups are needed to understand fully the injury and health risk associated with AR and to develop appropriate prevention strategies.